Idiomatic Expressions Used In Miss Peregrine’ Home For Peculiar Children Movie : A Pragmatics Analysis - Aditiawarman, Mac; Dhenisa Novela Twins, Dhenisa Novela Twins (Jurnal Ilmiah Pendidikan Scholastic, 2026)
This research is titled "Idiomatic Expressions Used in Miss Peregrine's Home for Peculiar Children Movie: A Pragmatics Analysis." This study discusses the form, type, and pragmatic function of idiomatic expressions used by the characters in the film. This research uses a descriptive qualitative method with O'Dell and Michael's (2010) theory of idioms and Miles and Huberman's (1994) data analysis model. Data was obtained thru observation and documentation techniques, namely by watching the movie repeatedly, recording dialogs containing idioms, and verifying them with the film script. Based on the research findings, 61 idiomatic data were found, consisting of equations, binomials, trinomials, proverbs, clichés, and fixed statements. The most dominant type of idiom was fixed statements (42.62%), followed by clichés (32.79%), and similes (16.39%), while trinomials were the least frequently found (1.64%). From a pragmatic function perspective, idioms serve to provide emphasis, make language sound more natural, describe social and cultural relationships, convey meaning implicitly, show the speaker's attitude or emotions, and act as a cohesive tool in narratives. This shows that idioms in the film Miss Peregrine's Home for Peculiar Children not only embellish the language but also enrich the cultural, emotional, and communicative